Tracing the Footsteps of Learning: A Qualitative Study of the Effectiveness of Active Learning Methods in Improving Student Focus at SDN 09 Tarung Tarung Selatan - Mai Saroh (BiCED Proceeding, 2024)
This study aims to improve students' understanding of the material "Belief in the Hereafter" at SDN 09 Tarung Tarung Selatan by applying an active learning method based on projects. The study was conducted using the Classroom Action Research (CAR) approach in two cycles. The results showed significant improvement in students' focus and understanding after the implementation of this method. In cycle I, the average score of students increased from 65 (pre-test) to 72 (post-test), with a participation rate of 60%. In cycle II, the average score increased to 82, with participation reaching 85%. The use of structured discussion guides, engaging learning media, and concrete examples helped students relate the material to real-life situations. This study proves that the active project-based learning method is effective in enhancing students' understanding.